Agregat Buatan Geopolimer Dengan Bahan Dasar Abu Terbang (Fly Ash) Dan Abu Sawit (Palm Oil Fuel Ash) - M Hari Bhakti; Monita Olivia; Alfian Kamaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Artificial geopolymer aggregates is one of many methods on making aggregates in case for substitution of natural aggregates. The main ingredients of thisgeopolymer is a material that contains silica and aluminium in a great numbers. In the province of Riau fly ash (FA) and palm oil fuel ash (POFA) are waste materials that until this time did not get utilized optimally whereas this materials are verypotentially for geopolymerization. NaOH and Na2SiO3 are used as alkaline activators, NaOH molarity (0, 8, 10 and 12M ) used as variation on sample composition. The highest compressive strength based on variation is using as the next sample artificial aggregates composition with 1-2cm size of diameters. Researchshowed that 12M variation results the highest compressive strength, that is 2,8 MPa for FA and 9,9 MPa for POFA. Based on that composition artificial geopolymer aggregates were made and then tested by its specific gravity, gradations andabrations.Keywords: artificial, aggregates, geopolymer, fly ash, palm oil fuel ash